ANALISIS EFISIENSI HARGA DAN BIAYA USAHATANI CABAI MERAH (CAPSIUM ANNUUM L) DI KECAMATAN WULUHAN KABUPATEN JEMBER - Nihliatun Ni'mah; Yuli Hariyati; Titin Agustina (University of Jember, 2017)
The productivity level of red chili in Wuluhan Sub-district in 2010 until 2015 has fluctuated. The level of productivity in red chili commodities in Wuluhan Sub-district is estimated to be influenced by several factors of production (fertilizer, pesticide, labor) and planting season. Some problems experienced by red chili farmers in Wuluhan Sub-district apart from productivity side of unstable but also from unstable selling price side. This research aims to determine (1) the influence of factors of production and planting season on productivity level of red chillies in Wuluhan Sub-district Jember District; (2) the efficiency of the price of the use of production factors at red chili farming in Wuluhan Sub-district, Jember District; (3) cost efficiency at red chili farming in Wuluhan Sub-district, Jember district. Location of research conducted by method of Purposive Method that is determination of research location done intentionally. Data collection methods used for primary data collection is the method of interview and questionnaire (questionnaire) while the data collection method used for secondary data collection is a documentation technique. The analytical tools used include: Cobb-Douglas production function, price efficiency and cost efficiency. The results showed that (1) production factors of pesticide, labor and planting season significantly affect productivity level; (2) The use of fertilizer, pesticide and labor production factor has not reached the price efficiency because the ratio between NPMxi and Pxi is more than one; (3) the use of cost is efficient, the business is run profitable and feasible to cultivate.